Formononetin, a novel FGFR2 inhibitor, potently inhibits angiogenesis and tumor growth in preclinical models - Wu, Xiao Yu (Oncotarget, 2015)
Most anti-angiogenic therapies currently being evaluated in clinical trials target vascular endothelial growth factor (VEGF) pathway, however, the tumor vasculature can acquire resistance to VEGF-targeted therapy by shifting to other angiogenesis mechanisms. Therefore, other potential therapeutic agents that block non-VEGF angiogenic pathways need to be evaluated. Here we identified formononetin as a novel agent with potential anti-angiogenic and anti-cancer activities. Formononetin demonstrated inhibition of endothelial cell proliferation, migration, and tube formation in response to basic fibroblast growth factor 2 (FGF2). In ex vivo and in vivo angiogenesis assays, formononetin suppressed FGF2-induced microvessel sprouting of rat aortic rings and angiogenesis. To understand the underlying molecular basis, we examined the effects of formononetin on different molecular components in treated endothelial cell, and found that formononetin suppressed FGF2-triggered activation of FGFR2 and protein kinase B (Akt) signaling. Moreover, formononetin directly inhibited proliferation and blocked the oncogenic signaling pathways in breast cancer cell. In vivo, using xenograft models of breast cancer, formononetin showed growth-inhibitory activity associated with inhibition of tumor angiogenesis. Moreover, formononetin enhanced the effect of VEGFR2 inhibitor sunitinib on tumor growth inhibition. Taken together, our results indicate that formononetin targets the FGFR2-mediated Akt signaling pathway, leading to the suppression of tumor growth and angiogenesis.